Inovasi Usaha Kecil Istri Nelayan sebagai Strategi Pemberdayaan Ekonomi Keluarga Pesisir [Innovation in Small Businesses Run by Fishermen’s Wives as a Strategy for Empowering the Economic Welfare of Coastal Families] - Maulani, Syifa Fajar; Nirmala, Ira; Tsani, Rubby Rahman; Rizky, Muhammad; Handayani, Melia; Hakim, Wafa Nurul; Ainiah, Siti Kurotul (UKInstitute, 2025)
Banten Province has a coastline of 896.063 km and a sea area of 11,500 km², making it a region with great fisheries potential. However, fishermen in this area, especially in Serang City, face economic challenges due to a lack of knowledge and access to technology for processing their catch. Most of the catch is sold directly at low prices without any processing. To improve the welfare of the fishing community, a community service team organized seminars and training sessions in Pekapuran Village. These activities taught fishermen’s wives how to process mackerel into high-value dim sum and introduced them to long-lasting packaging technology. The training involved 35 fishermen’s wives and used assessment methods including surveys, observation, interviews, and counseling. The results showed a significant increase in participants’ knowledge and interest in entrepreneurship. Understanding of women’s empowerment increased by 4.63%, interest in entrepreneurship rose by 8.42%, and knowledge of digital-based businesses increased by 13.52%. The training successfully boosted participants’ motivation and confidence to utilize local potential and digital technology to increase family income. This activity has the potential to drive economic growth for fishermen’s families in line with Sustainable Development Goals (SDGs) number 2 (no poverty) and number 8 (sustainable economic growth). Abstrak. Provinsi Banten memiliki garis pantai sepanjang 896,063 km dan perairan laut seluas 11.500 km², yang menjadikannya wilayah dengan potensi perikanan besar. Namun, nelayan di wilayah ini, khususnya di Kota Serang, menghadapi tantangan ekonomi karena kurangnya pengetahuan dan akses teknologi pengolahan hasil tangkapan. Kebanyakan hasil tangkapan dijual langsung dengan harga rendah tanpa pengolahan. Untuk meningkatkan kesejahteraan komunitas nelayan, tim pengabdian masyarakat mengadakan seminar dan pelatihan di Kampung Pekapuran. Kegiatan ini mengajarkan istri-istri nelayan cara mengolah ikan kembung menjadi dimsum bernilai jual tinggi, serta memperkenalkan teknologi pengemasan tahan lama. Pelatihan ini melibatkan 35 istri nelayan dengan metode assessment yang mencakup survei, observasi, wawancara, dan penyuluhan. Hasil kegiatan menunjukkan peningkatan signifikan dalam pengetahuan dan minat berwirausaha peserta. Pemahaman tentang pemberdayaan perempuan meningkat sebesar 4,63%, minat berwirausaha naik 8,42%, dan pengetahuan tentang usaha berbasis digital meningkat 13,52%. Pelatihan ini berhasil meningkatkan motivasi dan kepercayaan diri peserta dalam memanfaatkan potensi lokal dan teknologi digital untuk meningkatkan pendapatan keluarga. Kegiatan ini berpotensi mendorong pertumbuhan ekonomi keluarga nelayan sesuai dengan tujuan Sustainable Development Goals (SDGs) nomor 2 tanpa kemiskinan dan nomor 8 mengenai pertumbuhan ekonomi yang berkelanjutan.